Thoracic ultrasound as a predictor of pleurodesis success at the time of indwelling pleural catheter removal. Issue 3 (14th September 2020) - Chaddha, Udit; Agrawal, Abhinav; Bhavani, Sivasubramanium V.; Sivertsen, Kimberly; Donington, D. Jessica; Ferguson, Mark K.; Murgu, Septimiu
ABSTRACT: Background and objective: IPC in patients with MPE are removed within 3 months in 30–58% of cases, usually due to decreased pleural fluid output as a result of pleurodesis. Disease control can also account for the lack of fluid output, potentially explaining why 4–14% of patients undergo repeat pleural intervention for fluid re‐accumulation (at the time of disease recurrence or progression). The aim of our pilot study is to determine the accuracy of thoracic ultrasound (TUS) in predicting pleurodesis success in patients with MPE at the time of IPC removal. Methods: This is a single‐centre, prospective observational cohort study that enrolled consecutive patients with confirmed MPE treated with IPC at the time of IPC removal. TUS was performed to calculate a PAS. Patients were followed up for a minimum of 3 months. Failure was defined as pleural fluid recurrence within 3 months. Results: Twenty‐seven patients were screened and 25 were included in the final analysis. Pleurodesis success was observed in 88% ( n = 22) and failure in 12% ( n = 3) of patients. The mean PAS was higher in patients with pleurodesis success (22.0 vs 9.3, P = 0.01). A PAS greater than 10 predicted pleurodesis success with a sensitivity of 100% and specificity of 86%. Conclusion: This pilot study suggests that TUS at the time of IPC removal accurately identifies patients who have achieved pleurodesis and therefore will not have re‐accumulation of pleural effusion or require an ipsilateral pleural intervention for at least 3 months post‐IPC removal. Abstract : Our pilot study demonstrates that thoracic ultrasound (TUS) at the time of IPC removal can accurately determine pleurodesis success and identify patients in whom the effusion may recur. A PAS of greater than 10 predicted pleurodesis success with a sensitivity of 100% and specificity of 86%.